2023
DOI: 10.3389/fendo.2023.1161402
|View full text |Cite
|
Sign up to set email alerts
|

Liver-bone crosstalk in non-alcoholic fatty liver disease: Clinical implications and underlying pathophysiology

Abstract: Osteoporosis is a common complication of many types of chronic liver diseases (CLDs), such as cholestatic liver disease, viral hepatitis, and alcoholic liver disease. Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent metabolic liver disease, affecting almost one third of adults around the world, and is emerging as the dominant cause of CLDs. Liver serves as a hub for nutrient and energy metabolism in the body, and its crosstalk with other tissues, such as adipose tissue, heart, and brain, has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Moreover, Dichtel et al showed that decreased IGF-1 levels were correlated with higher histological severity of NAFLD (60). Decreased IGF-1 have been reported in both patients with osteoporosis and NAFLD, indicating the important role of IGF-1 in the liver-bone axis (58).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Dichtel et al showed that decreased IGF-1 levels were correlated with higher histological severity of NAFLD (60). Decreased IGF-1 have been reported in both patients with osteoporosis and NAFLD, indicating the important role of IGF-1 in the liver-bone axis (58).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor-1 (IGF-1) is mainly secreted by the liver while is also locally produced in small amounts by bones, affecting positively bone remodeling (58). Yao et al in their metanalysis demonstrated that IGF-1 levels were decreased in patients with NAFLD compared to healthy controls (59).…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the metabolic center involving not only in the metabolism of micro- and macro-nutrients (glucose, fat, protein, vitamins) nourishing the bones but also the synthesis of a variety of signaling molecules such as cytokines and enzymes into the circulation to modulate the metabolism and function of the bones [ 4 ]. Patients with chronic liver disease may experience abnormal metabolic changes in bones, known as hepatic osteodystrophy commonly manifested as decreased BMD and osteoporosis [ 5 , 6 ]. Alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD) are two major types of chronic liver diseases marked by a variety of abnormalities in the liver, including fatty liver disease, liver fibrosis, and cirrhosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%